Historical Shear Experiments of RC Beams in Hungary and their Effect on Change of Shear Design - Ther, Péter Pál; Sajtos, István (Periodica Polytechnica Civil Engineering, 2023)
The shear behavior is one of the most mysterious physical phenomena of an RC (reinforced concrete) beam. Many shear-transfer actions (such as dowel action, cantilever action, aggregate interlock, tension softening, etc.) affect it. Still, there is no scientific agreement on the number and the role of these phenomena. The paper investigates the historical development of these shear-transfer actions and the calculation models made from them through the glass of experimental research in the last one and half centuries in Hungary, in the context of the current international state of the art. This historical approach gives us an understanding of how the researchers and engineers of the past tried to understand the structure, and it leads us to accept that we are also on the way to understanding the shear behavior. However, the perfect model and understanding are far away from now. But are we on the right way?